2014
DOI: 10.1016/j.vetpar.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Body condition score as a selection tool for targeted selective treatment-based nematode control strategies in Merino ewes

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 BCS response, and liveweight responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
1
24
1
1
Order By: Relevance
“…This will become worse as none of the monitored properties have more than two drug options to define an effective chemical parasitic control strategy. There is no doubt that this scenario should also be a concern for other regions (GETACHEW et al, 2007;VÁRADY et al, 2011;CORNELIUS et al, 2014;FALZON et al, 2014), especially for those countries that border the state (Argentina and Uruguay).…”
Section: Discussionmentioning
confidence: 99%
“…This will become worse as none of the monitored properties have more than two drug options to define an effective chemical parasitic control strategy. There is no doubt that this scenario should also be a concern for other regions (GETACHEW et al, 2007;VÁRADY et al, 2011;CORNELIUS et al, 2014;FALZON et al, 2014), especially for those countries that border the state (Argentina and Uruguay).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations observed that anthelmintic treatments provide a differentially-greater effect in low-BCS ewes in preventing further weight and condition decline (Cornelius et al, 2014), suggesting that BCS can therefore serve as an appropriate index for TST strategies. Earlier studies within this Mediterranean environment also utilised BCS as a TST selection index (Besier et al, 2010).…”
Section: The Use Of Bcs As a Tst Selection Index Has Been The Subjectmentioning
confidence: 99%
“…This outcome was based on in vivo data from flocks representative of commonly-occurring nutritional and parasitological situations observed in Mediterranean regions of Australia. However, given the results from previous work (Cornelius et al, 2014) it would be advised that sheep below a pre-determined BCS be included in the treatment group to minimise the risk of losses and compromised welfare in low-BCS sheep. The present studies also confirmed that substantial proportions of an adult ewe flock in good body condition could be left untreated without significant production loss, at least where environmental conditions that minimise re-infection from pastures are present.…”
Section: The Use Of Bcs As a Tst Selection Index Has Been The Subjectmentioning
confidence: 99%
See 2 more Smart Citations